Critical Factors that Determine Credit Approval to Micro, Small, and Medium Enterprises (MSME) IN BEKASI - Halim Putera Siswanto; Agus Zainul Arifin; Cavin Cavin (Faculty of Economic and Business, 2019)
Many business owners attempt to apply for bank credit, but not all of them are approved. This study aims to reveal the factors determining credit approval to Micro, Small, and Medium Enterprises (MSME). The variables used in this study are the owner's capital, company establishment, collateral value, credit amount, owner's age, and good relationship with the bank. In this study, the logit model used as a technique of analysis, in which there is only one dependent variable in the form of dummy along with the other six independent variables. The statistical test reveals that simultaneously all independent variables have significant effects on credit approval. Partially, only the owner's capital and good relationships with the bank do affect the approval. Therefore, business owners should pay more attention to their amount of capital and interrelation with the bank when applying for bank credit.JEL Classification: C30, G21